Crucial confrontations : tools for resolving broken promises, violated expectations, and bad behavior - Patterson, Kerry, 1946- (McGraw-Hill, 2005)
The authors of Crucial Conversations furnish a selection of tools to help resolve touchy, controversial issues in the office and at home, including how to determine whether an issue is worth confronting, how to avoid jumping to nasty conclusions, how to decide which problems to handle and in what order, and how to motivate people without threats.